2007
DOI: 10.1073/pnas.0700735104
|View full text |Cite
|
Sign up to set email alerts
|

JARID1B is a histone H3 lysine 4 demethylase up-regulated in prostate cancer

Abstract: Histone methylation is a dynamic process that participates in a diverse array of cellular processes and has been found to associate with cancer. Recently, several histone demethylases have been identified that catalyze the removal of methylation from histone H3 lysine residues. Through bioinformatic and biochemical analysis, we identified JARID1B as a H3K4 demethylase. Overexpression of JARID1B resulted in loss of tri-, di-, and monomethyl H3K4 but did not affect other histone lysine methylations. In vitro bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
331
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 349 publications
(341 citation statements)
references
References 36 publications
10
331
0
Order By: Relevance
“…The genes JARID1B and KDM4A were described before as highly expressed in PrCa, and function as coactivators of AR (Shin and Janknecht, 2007;Xiang et al, 2007). In contrast, PHF8 mRNA was not previously described as significantly (Po0.0001) overexpressed in PrCa versus normal prostate.…”
Section: Phf8 Is Overexpressed In Prca and Reduces Prca Cell Prolifermentioning
confidence: 92%
See 1 more Smart Citation
“…The genes JARID1B and KDM4A were described before as highly expressed in PrCa, and function as coactivators of AR (Shin and Janknecht, 2007;Xiang et al, 2007). In contrast, PHF8 mRNA was not previously described as significantly (Po0.0001) overexpressed in PrCa versus normal prostate.…”
Section: Phf8 Is Overexpressed In Prca and Reduces Prca Cell Prolifermentioning
confidence: 92%
“…Eight KDMs are highly expressed in PrCa's (Metzger et al, 2005;Kahl et al, 2006;Wissmann et al, 2007). Various HDACs and KDMs were shown to regulate androgen receptor (AR)-mediated transcription, thus affecting gene expression patterns essential for PrCa proliferation, development and progression (Yamane et al, 2006;Wissmann et al, 2007;Wolf et al, 2007;Xiang et al, 2007;Welsbie et al, 2009). Despite the emerging role of epigenetic processes and large scale mapping of cancer-associated chromatin modifications in PrCa, the functional significance of key 'readers', 'writers' and 'erasers' has not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Although significant expression of PLU-1 is restricted to testis and only low levels of PLU-1 are seen in other normal adult tissues, its expression increases markedly in pathological conditions such as malignant breast cancer, metastatic prostate cancer and testis cancer (Table 1). 27,28 Based on its overexpression in cancer, PLU-1 was suggested as a testis cancer antigen. Yamane et al have shown the oncogenic potential of PLU-1 at the cellular level.…”
Section: Plu-1/jarid1b/kdm5bmentioning
confidence: 99%
“…However, the mutants showed decreased demethylase activity for both H3K9me2 and H3K27me2 in vivo when their effect was examined in insect cells ( Figure 5B). We also made attempts to deplete H3K4me3 by its demethylase Jarid1b [30], at the same time as or prior to infection by ceKDM7A-expressing virus, but we were unable to quantify the results when the cells were infected simultaneously or sequentially. Nevertheless, our results indicate that the PHD domain-mediated H3K4me3 binding is required for the demethylase activity of ceKDM7A in vivo.…”
Section: Disruption Of the Phd Domain Binding To H3k4me3 Reduced The mentioning
confidence: 99%